Security Evaluation of IOS and Android - Ahmet HAYRAN; Muratcan IĞDELI; Atif YILMAZ; Cemal GEMCI (International Journal of Applied Methods in Electronics and Computers, 2016)
In the race of smartphone operation systems, IOS and Android seem to have the big part of pie. Both platforms have grown more enterprise-friendly since about one decade. Their adaptable functionalities make people’ lives easy and give them a reputation in the current competitive technology world. We all have our personal thoughts it comes to features, usability and design. However, what about security? Mobile devices, smartphone operation systems run on, hold valuable, sensitive and classified information or content. So, that increases their attractiveness as targets for cybercriminals. The security of these devices is a growing concern and focus point for smartphone users. Eventually, the security technology of the smartphones becomes one of the prime research and these smartphone vendors have increasingly focused on security in their design efforts. In this paper, factors that influence security within IOS and Android are studied to promote the discussion. Security technologies of IOS and Android are briefly presented. And, varies factors are considered such as methods of application distribution, reduced attack surface, privilege separation, permission-based access control, sandboxing, data encryption, data execution prevention and address space layout randomization, geo-location and auto-erase. Then, brief information is given about malicious apps. Lastly, discussion is concluded to answer that tight question in the light of security models investigation and evidences collected from current life.